x^3+9x^2+27x-27=-8 (tìm x )
x3 + 9x2 + 27x + 27 = 0
( x - 2 ) x - x2 (x - 6) = 4
27x3 - 27x2 + 9x - 1 = 8
(x - 1 )3 - (x + 3) . (
a: \(\Leftrightarrow\left(x+3\right)\left(x^2-3x+9\right)+9x\left(x+3\right)=0\)
=>(x+3)(x^2+6x+9)=0
=>x=-3
b: \(\Leftrightarrow x^2-2x-x^3+6x^2-4=0\)
=>-x^3+6x^2-2x-4=0
hay \(x\in\left\{5.5;1.14;-0.64\right\}\)
c: =>(3x-1)^3=8
=>3x-1=2
=>3x=3
=>x=1
`1-27x^3`
`x-3^3 +27`
`27x^3 +27x^2 +9x+1`
`(x^6)/27 - (x^4 y)/3 +x^2 y-y^3`
Phân tích thành nhân tử
\(1-27x^3\)
\(=1-\left(3x\right)^3\)
\(=\left(1-3x\right)\left(1+3x+9x^2\right)\)
\(---\)
\(x-3^3+27\)
\(=x-27+27=x\)
\(---\)
\(27x^3+27x^2+9x+1\)
\(=\left(3x\right)^3+3\cdot\left(3x\right)^2\cdot1+3\cdot3x\cdot1^2+1^3\)
\(=\left(3x+1\right)^3\)
\(---\)
\(\dfrac{x^6}{27}-\dfrac{x^4y}{3}+x^2y^2-y^3\) (sửa đề)
\(=\left(\dfrac{x^2}{3}\right)^3-3\cdot\left(\dfrac{x^2}{3}\right)^2\cdot y+3\cdot\dfrac{x^2}{3}\cdot y^2-y^3\)
\(=\left(\dfrac{x^2}{3}-y\right)^3\)
#Ayumu
1-27x\(^3\)
=(1-3x)(1+3x+9x\(^2\)
a.(x+1)^2-25
b. 1-4x^2
c. 8-27x^3
d. 27+27x+9x^2+x^3
e. 8x^3-12x^2y+6xy^2-y^3
f. x^3+8y^3
g. x^5-3X^4+3x^3-x^2
a: \(=\left(x+1+5\right)\left(x+1-5\right)=\left(x+6\right)\left(x-4\right)\)
b: =(1-2x)(1+2x)
c: \(=\left(2-3x\right)\left(4+6x+9x^2\right)\)
d: =(x+3)^3
e: \(=\left(2x-y\right)^3\)
f: =(x+2y)(x^2-2xy+4y^2)
tìm x: x^3-6x^2+12x-8=0
b)16x^2-9(x+1)^2+0
c)-27+27x-9x^2+x^3=0
d)x^2-6x+5=0
d) <=>x2-5x-x+5=0
<=>x(x-5)-(x-5)=0
<=>(x-5)(x-1)=0
<=>x=5 hoặc x=1
Tìm x biết:
a) x3 - 6x2 + 12x - 8 = 0
b)x3 + 9x2 +27x + 27 = 0
a ) \(x^3-6x^2+12x-8=0\)
\(\Leftrightarrow x^3-3.x^2.2+3.x.2^2-2^3=0\)
\(\Leftrightarrow\left(x-2\right)^3=0\)
\(\Leftrightarrow\left(x-2\right)=0\)
\(\Leftrightarrow x=2\)
b ) \(x^3+9x^2+27x+27=0\)
\(\Leftrightarrow x^3+3.x^2.3+3.x.3^2+3^3=0\)
\(\Leftrightarrow\left(x-3\right)^3=0\)
\(\Leftrightarrow\left(x-3\right)=0\)
\(\Leftrightarrow x=3\)
a) x3 - 6x2 + 12x - 8 = 0
( x - 2 ) 3 = 0
x - 2 = 0
x = 2
b) x3 + 9x2 + 27x + 27 = 0
( x + 3 )3 = 0
x + 3 = 0
x = -3
Tìm x biết x3 + 9x2 + 27x + 27=97
tìm a b c để (x^4+ax^3+bx+c) chia hết cho (x^3-9x^2+27x-27)
-27+27x-9x2+x=0. Tìm x
=> -9x2 + 28x - 27 = 0
=> \(\Delta\)' = b'2 - ac = 142 - [ (-9) . (-27) ] = -47 < 0
vì denta nhỏ hơn 0 nên => pt vô nghiệm
Tìm x:
a) x3-9x2+27x-27=0
b) x3-25x=0
c)9x2-1=0
a) x3-9x2+27x-27=0
<=>(x-3)3=0
<=>x-3=0
<=>x=3
b) x3-25x=0
<=>x.(x2-25)=0
<=>x.(x-5)(x+5)=0
<=>x=0 hoặc x-5=0 hoặc x+5=0
<=>x=0 hoặc x=5 hoặc x=-5
c)9x2-1=0
<=>(3x-1)(3x+1)=0
<=>3x-1=0 hoặc 3x+1=0
<=>x=1/3 hoặc x=-1/3
a, x^3 - 9x^2 + 27x - 27 = 0
=> ( x - 3)^3 = 0
=> x - 3 = 0
=> x = 3
b, x^3 - 25x = 0
=> x(x^2 - 25) = 0
=> x(x-5)(x + 5) = 0
=> x =0 hoặc x - 5 = 0 hoặc x + 5 = 0
=> x= 0 hoặc x =5 hoặc x = -5
c, 9x^2 - 1 = 0
=> (3x)^2 - 1^2 = 0
=> ( 3x- 1)(3x+ 1) = 0
=> 3x - 1 = 0 hoặc 3x + 1 = 0
=> x = 1/3 hoặc x = -1/3